Perlindungan Hukum Rumah Sakit Yang Belum Memenuhi Kelas Rawat Inap Standar JKN - Deny Sulistyorini; Mokhamad Khoirul Huda (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract— This study aims to analyze the parameters of the JKN standard inpatient class and the legal consequences for the hospital if it cannot meet the JKN standard inpatient class rules. This research uses descriptive normative research method. The approach used is the statutory approach, conceptual approach, and comparative approach. The results show that the definition and criteria for standard inpatient classes have not been regulated in the regulations on standard classes for JKN participants, either in the form of laws, government regulations, presidential regulations or ministerial-level regulations. The process of phasing the application of standard inpatient classes and the consequences of the hospital if it cannot meet these rules also there is no regulation that regulates it. The current regulations are considered to be insufficient to provide protection for hospitals in implementing standard inpatient classes. Strengthening regulations governing the parameters of standard inpatient classes and the phasing process for implementing standard inpatient classes, which is then followed by outreach to stakeholders, hospitals and JKN participants, as well as the role of ministries/agencies in overseeing the phasing process.